Paraneoplastic ataxia and dystonia secondary to a malignant fibrous histiocytoma. (12th November 2010) - Dolan, Ross; Thomas, Ralph; O'Riordan, Jonathan I
Abstract : Paraneoplastic movement disorders are part of the spectrum of paraneoplastic syndromes caused by the production of onconeural antibodies such as anti-Hu by underlying tumours. These attack specific neurons depending on receptor aetiology. We report the case of a 53-year-old man who presented 8 years previously with symptoms of upper limb weakness, light headedness, dizziness and falls. His condition followed a progressive course. Two years after onset he had right-sided weakness, diplopia and generalised dystonia. Initial investigations identified a positive anti-Hu antibody, but an extensive search for a primary tumour was negative. A malignant fibrous histiocytoma in his right gluteal fold was subsequently identified. At this stage he was bed bound with severe ataxia, dystonia and spasticity. Following surgical excision and treatment with high dose steroids and pulse immunoglobulin, further progression was arrested and minor improvements occurred. He can now ambulate with bilateral assistance but remains severely disabled.